Fibronectin synthesis in subretinal membranes of proliferative vitreoretinopathy. Issue 8 (August 1992) - Hiscott, P; Waller, H A; Grierson, I; Butler, M G; Scott, D L; Gregor, Z; Morino, I
Abstract : In situ hybridisation and immunohistochemical studies were conducted on six surgically excised subretinal membranes of proliferative vitreoretinopathy to investigate whether displacement of retinal pigment epithelial and glial cells to subretinal membranes was associated with fibronectin production by the subretinal membrane cells. Fibronectin messenger RNA (mRNA) and fibronectin immunoreactivity were observed in some cells in all of the subretinal membranes studied and up to 30% of the cells in individual specimens showed intense labelling for fibronectin mRNA. The results support the concept that the cells in subretinal membranes produce fibronectin. Locally produced fibronectin may play a role in subretinal membrane cohesion, and displacement of retinal pigment epithelial and glial cells from their normal location may induce the cells to manufacture fibronectin. Fibronectin production may be more prominent in migrating subretinal cells.